2017
DOI: 10.4149/av_2017_02_10
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of insulin resistance markers in Pakistani patients suffering from HCV-associated type 2 diabetes mellitus

Abstract: The current study was designed to determine the role of the host genes involved in the development of chronic hepatitis C-associated type 2 diabetes mellitus. This study was carried out in patients in four different stages of chronic hepatitis C virus (HCV) infection, including treatment-naïve HCV patients, HCV-positive patients with type 2 diabetes mellitus (T2DM), non-responders and responders. The mRNA expression level of host genes, such as glucose-6-phosphatase (G6Pase), tumor necrosis factor α (TNF-α) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Moreover, secretion of soluble endocrine mediators from infected hepatocytes may contribute to IR in extrahepatic tissues [29,30]. In a study of chronic HCV-infected patients with or without T2DM and healthy controls, chronic HCV infection was associated with IR and upregulation of tumour necrosis factor-a, glucose-6-phosphatase and resistin, leading to gluconeogenesis [35]. Development of HCV-induced IR may be influenced by host-related genetic and environmental factors, and with additional contributions from an imbalance of adipocytokine profile and the presence of liver steatosis, may result in progression to T2DM [36].…”
Section: What Are the Proposed Pathogenic Mechanisms Underlying The Association Between T2dm And Chronic Hcv Infection?mentioning
confidence: 99%
“…Moreover, secretion of soluble endocrine mediators from infected hepatocytes may contribute to IR in extrahepatic tissues [29,30]. In a study of chronic HCV-infected patients with or without T2DM and healthy controls, chronic HCV infection was associated with IR and upregulation of tumour necrosis factor-a, glucose-6-phosphatase and resistin, leading to gluconeogenesis [35]. Development of HCV-induced IR may be influenced by host-related genetic and environmental factors, and with additional contributions from an imbalance of adipocytokine profile and the presence of liver steatosis, may result in progression to T2DM [36].…”
Section: What Are the Proposed Pathogenic Mechanisms Underlying The Association Between T2dm And Chronic Hcv Infection?mentioning
confidence: 99%
“…In addition to hepatic steatosis, several studies have reported the correlation of hepatitis C virus and diabetes mellitus . As we all know, obesity and lipid metabolism disorders often affect glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sirt1-mediated In addition to hepatic steatosis, several studies have reported the correlation of hepatitis C virus and diabetes mellitus. [37][38][39] As we all know, obesity and lipid metabolism disorders often affect *Indicates a significant difference compared with the WT + Vector group and **indicates a significant difference compared with the WT + 1b group. (Data are shown as the mean ± SEM, n = 7-8/group, * or **P < .05.)…”
Section: Discussionmentioning
confidence: 99%